Prevalence and Association of Malaria With the Blood Group on Febrile Patients at Woldia Comprehensive Specialized Hospital, Northeast Ethiopia - Wagaw Abebe; Fasikaw Wudu; Gebreeyesus Derib; Foziaya Fentie; Agenagnew Ashagre (Journal of Parasitology Research)
Conclusion and Recommendation: The total number of microscopically confirmed malaria parasites was 8.3%. P. falciparum was dominant over P. vivax. Individuals with blood group O were less likely to get severe malaria than those with other blood groups. Based on the findings of this study, we recommend that additional studies investigate the probable relationship between the ABO blood group phenotype and malaria infection.